1998
DOI: 10.1007/s004420050684
|View full text |Cite
|
Sign up to set email alerts
|

Hourglass and rhythmic components of photoperiodic time measurement in the pitcher plant mosquito, Wyeomyia smithii

Abstract: The mosquito, Wyeomyia smithii, enters a larval dormancy or diapause that is initiated, maintained, and terminated by photoperiod. The median or critical photoperiod regulating diapause increases from 12 h of light per day along the Gulf of Mexico, USA (30° N), to over 15 h in southern Canada (49° N). Photoperiodic time measurement in W. smithii comprises both rhythmic and hourglass (interval timer) components. Using interrupted-night and resonance experiments, we show that both the rhythmic and hourglass comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…In response to short‐day conditions, the third‐ or fourth‐instar W. smithii larvae enter diapause (Bradshaw & Lounibos, ). Formal, classical experiments show that a weak dampening oscillator participates in photoperiodic induction of diapause in W. smithii (Wegis et al ., ; Bradshaw et al ., ) and also that the influence of this oscillator decreases in populations living at high latitudes (Bradshaw & Holzapfel, ). Bradshaw & Holzapfel () assume that the circadian clock of W. smithii is robust and argue that it would appear to be maladaptive to couple the robust circadian clock to the highly variable and rapidly evolving photoperiodic calendar.…”
Section: Discussionmentioning
confidence: 99%
“…In response to short‐day conditions, the third‐ or fourth‐instar W. smithii larvae enter diapause (Bradshaw & Lounibos, ). Formal, classical experiments show that a weak dampening oscillator participates in photoperiodic induction of diapause in W. smithii (Wegis et al ., ; Bradshaw et al ., ) and also that the influence of this oscillator decreases in populations living at high latitudes (Bradshaw & Holzapfel, ). Bradshaw & Holzapfel () assume that the circadian clock of W. smithii is robust and argue that it would appear to be maladaptive to couple the robust circadian clock to the highly variable and rapidly evolving photoperiodic calendar.…”
Section: Discussionmentioning
confidence: 99%
“…Saunders and Bertossa, 2011 proposed that this concept 'could be tested by using classical night interruption experiments in 24 h L:D cycles (Saunders, 2010a, b) to determine the time of night at which this phase occurs in different latitudinal strains.' Indeed, we have already run just such night-interruption experiments and have shown that the phases of maximum response do not change with respect to either dawn or dusk among six populations from 30-491N in either 24-or 48-h light-dark cycles and over a 3.25-h difference in CPP among these populations (Bradshaw et al, 1998). Hence, the evolution of critical photoperiod in W. smithii has not involved a shift in the light-sensitive phase of photoperiodic induction.…”
Section: Discussionmentioning
confidence: 99%
“…In numerous insect species, critical photoperiods regularly increase with decreasing latitude (Danilevski, 1965; Tauber et al ., 1986; Danks, 1987). Such geographical clines of the critical photoperiods are now assumed to be adaptive products of natural selection acting locally on the timing of diapause (Taylor & Spalding, 1986; Bradshaw, Holzapfel & Davidson, 1998). Within populations of the freshwater copepod Diaptomus sanguineus (Forbes), adaptive response to fluctuating selection for fish predation avoidance was favoured by genetic variation associated with the timing of the production of diapausing eggs (Hairston & Munns, 1984; Hairston & Dillon, 1990).…”
Section: Discussionmentioning
confidence: 99%